From mechanisms to therapeutics: molecular insights into gastrointestinal injury under high-altitude hypoxia - Yu, Yonglu; Zhang, Yan; Yang, Yunsheng (Frontiers in Microbiology, 2026)
The extreme environmental conditions of a plateau have an important impact on the economic development of the area, including tourism and employment. High-altitude environments, characterized by hypoxia, low atmospheric pressure, and intense ultraviolet radiation, are recognized as key contributors to gastrointestinal injury. These environmental stresses promote oxidative stress, inflammatory responses, and gut microbiota dysbiosis, resulting in intestinal barrier disruption, increased permeability, and immune imbalance, which collectively predispose individuals to gastrointestinal disorders and multi-organ dysfunction. Accumulating evidence suggests that natural bioactive molecules, probiotics, and synbiotics exert protective effects against high-altitude-induced intestinal injury via diverse mechanisms. Accordingly, this review focuses on the key mechanisms of high-altitude hypoxia-induced intestinal injury and discusses the therapeutic potential of intestinal function-enhancing molecules. This work aims to offer a theoretical framework and identify potential intervention targets for the management of gastrointestinal disorders associated with high-altitude exposure.